OPTIMALISASI PAJAK DAN RESTRIBUSI DAERAH PEMERINTAH KOTA SAMARINDA - Ashari, Arifah; Robert Hutauruk, Martinus; Mansyur (OBOR: Oikonomia Borneo, 2022)
The research aims to find out the Realiasi of Taxes and Regional Retributions of the Government of Samarinda City whether it has been Optimal or not in terms of Realization of Tax Revenue and Regional Retribution. And to know which Taxes and Retributions are not optimal. This research is descriptive qualitative research and to collect data used purposive sampling. Data collection methods used are interviews, observation and documentation. Data analysis techniques used are Data Collection, Data reduction, Data presentation and Withdrawal Conclusions. Based on the results of the study that there are several objects of tax and regional levies that have revenue realization that exceeds the budget target and there are also some tax objects and provincial levies which the level of revenue realization still needs to be more optimized.